Wind turbine doubly-fed induction generator defects diagnosis using rotor currents lissajous curves - Sara Kharoubi; Lamiaa El Menzhi (Institute of Advanced Engineering and Science, 2020)
Nowadays, inverters are power electronics devices used in the renewable energy conversion systems. Therefore, the continuity of service of power converter has been a major concern. In this paper, a technique for diagnosing multiple open switch faults in three phase voltage inverters feeding Doubly Fed Induction Generator DFIG is presented. It is based on the so-called the Lissajous curves of DFIG rotor currents. For this purpose, the modeling of a non-defected wind conversion system based on mathematic model created in Matlab Simulink is firstly presented, after that, an indirect stator field vector-oriented control is applied to obtain the wind system performance. Finally, rotor currents Lissajous curves are analyzed in case of a non-defected and defected inverter. Simulation results show the effectiveness of the proposed method